Preliminary Research on a High Thrust-to-Weight Ratio of Double-Sided Composite Impeller Microturbine Engine - Cheng Zhang; Bei Yang; Yun Wang; Gaoxing Tu (International Journal of Aerospace Engineering)
In some situations, the improvement of the thrust-to-weight ratio (TWR) of microturbine engines (MTEs) for energy-, economic-, and environment-related reasons can be achieved for military or civilian purposes. However, due to limitations of existing traditional MTE technology, it is difficult to meet the key requirements of small aircraft for high energy/power density and low-cost power, especially for long-endurance drone swarms. To address these problems, a novel compact concept of a high-TWR of MTE with a double-sided composite impeller (DSCI) is proposed in this research. First, the principle and structure of the concept are explained through theoretical analysis, and its potential advantages are discussed. Second, the DSCI is analyzed at the top level, and the design principle and important parameters are discussed. The DSCI and supporting jet engine are preliminarily designed. Then, their weight is estimated. Finally, theoretical analytical and numerical simulations are used to preliminarily research the performance parameters of DSCI jet engine at the design point, and the parameters are discussed. These calculations showed encouraging results, with all components of the DSCI jet engine meeting matching characteristics. Compared to the JetCat P500-PRO-GH, the DSCI jet engine has a 39.4% increase in TWR and a 36.82% decrease in specific fuel consumption (sfc). This study lays a foundation for the development of high energy/power density MTEs in the future.